Decreased expression of lncRNA Malat1 in rat spinal cord contributes to neuropathic pain by increasing neuron excitability after brachial plexus avulsion - Meng, Chong (J Pain Res, 2019)
Purpose: Neuropathic pain (NP) is a challenging clinical problem due to its complex pathogenesis. In our previous study using microarray, we found that the levels of lncRNA Malat1 were decreased in the spinal cord of NP rat after brachial plexus avulsion, but its contribution to NP remain unclear. The purpose of this study was to investigate its role in the pathogenesis of NP. Methods: In the NP model of complete brachial plexus avulsion rat, spinal cords were harvested, and fluorescence in situ hybridization (FISH) was used to test the spatial expression of Malat1 and qRT-PCR was used to confirm the quantitative expression of Malat1. In primary cultured neurons, Malat1 expression interfered with adenovirus. Spontaneous electric activities of neurons were tested using multi-electrode arrays and apoptosis of neurons was tested using TUNEL method. The change of intracellular calcium concentration was analyzed using calcium imaging method. Results: Decreased Malat1 expression was confirmed using qRT-PCR, and Malat1 was identified in the cytoplasm of neurons in spinal cord, but not in glia. In vitro, the decrease of Malat1 resulted in an increase in the frequency of spontaneous electric activity in neurons but had no effect on neuronal apoptosis. Further analysis indicated during glutamate stimulation, the change of intracellular calcium concentration in neurons with downregulated Malat1 expression was significantly greater than that in normal neurons. Conclusion: Reduced Malat1 expression may induce NP by increasing neuronal excitability in the spinal cord via regulation of calcium flux.